Analisis Penerapan Prinsip-Prinsip Syariah Pada Akad Tabarru di Produk Asuransi Syariah ( Studi Kasus Asuransi Prudential Cabang Sampang ) - Laylati Alifatul Mutmainah; Dwiyani Sudaryanti; Harun Al Rasyid (El-Aswaq: Islamic Economics and Finance Journal, 2021)
This study was used to determine the analysis of sharia principles in the insurance PrudentialIndonesia Sampang branch. This research includes qualitative methods, with interview anddocumentation data collection techniques. The principles applied to Prudential insurance in theSampang branch are: 1) mutual assistance, 2) justice, 3) trustworthiness, 4) willingness, 5)monotheism, 6) prohibition of usury, 7) prohibition of maysir, 8) prohibition of gharar. With theresults of Prudential Indonesia Insurance, the Sampang Branch has implemented shariaprinciples in accordance with the DSN-MUI Fatwa No.21/DSN-MUI/X/2001 concerning generalguidelines for sharia insurance, DSN-MUI Fatwa. The mechanism for managing tabarru' fundsat Prudential Indonesia's Sampang Branch is in accordance with DSN-MUI Fatwa NO. 53/DSNMUI/III/2006 concerning tabarru' contracts in sharia insurance, DSN-MUI Fatwa No. 81/DSNMUI/III /2011 Regarding the refund of tabarru' for insurance participants who quit before theend of the agreement period.